Implementation of Islamic Campus Values Based on Human Rights and Wasathiyyah Islam - Erlan Dwi Cahyo; Andri Nirwana AN; Nur Rizqi Febriandika; Tipmanee Sriplod (Cakrawala: Jurnal Studi Islam, 2022)
Wasathiyyah Islam and human rights are one of the many terminologies that appear in Islamic thought, especially in counteracting radicalism. In the context of Muhammadiyah universities, all activities are recommended to refer to the Guidelines for Islamic Life for Muhammadiyah Members (PHIWM). This study aims to identify the implementation of Islamic values based on human rights and Wasathiyyah Islam in Muhammadiyah universities. This study used a qualitative method through a literature review approach. The results of the study revealed that the Al-Islam and Kemuhammadiyahan Development Institute is the motor for implementing Wasathiyyah Islamic values and human rights in Muhammadiyah universities. One of the main programs is the obligation to follow baitul arqam for the entire Muhammadiyah academic community.